The impact of Philippines' conditional cash transfer program on consumption - Melba V. Tutor (University of the Philippines, School of Economics (UPSE), 2014)
Pantawid Pamilyang Pilipino Program provides cash grants to poor households conditional on pre-determined investments in human capital. This study analyzed its impact on consumption using the 2011 Annual Poverty Indicators Survey. Average treatment effect on the treated (ATT) is estimated through propensity score matching methodology. Heterogeneous impacts are examined among the bottom 20% of income distribution. The study finds that among the total sample, per capita total expenditures is not affected by the program. In per capita monthly terms, only carbohydrates and clothing significantly increased. As expenditure shares, education and clothing registered significant positive impact. No impact is observed on health spending, both in per capita terms and as a share of expenditure. The impact of Pantawid Pamilya on consumption is more pronounced among the poorest fifth of households. Results show that households have responded to program conditionalities but there is very little room to improve consumption of other basic needs. The recent program modification of increasing education grants to older children and covering up to secondary school completion will help households sustain induced behavioral changes over time. Stronger impact on the poorest fifth of households underscores the need to improve the targeting mechanism to address leakage issues.
Keywords: I38; D12; 330; consumption; CCT; impact evaluation; propensity score matching